The Role of Digital Media in Building the Image of Saka Tunggal Mosque: A Media Discourse Analysis - Muttaqin, Hermansyah; Sigied Himawan Yudhanto, (Journal of Pragmatics Research, 2025)
In today's digital world, online media significantly shapes our perception of cultural and religious sites. For example, the Saka Tunggal Mosque. The Saka Tunggal Mosque, one of Indonesia's oldest mosques, is a prime example. The digital sphere has profoundly influenced its image. This study delves into the unique digital narrative surrounding the Saka Tunggal Mosque, employing a Media Discourse Analysis approach. Using a descriptive qualitative methodology, we will analyze data from social media, news websites, and Islamic blogs, all through the lens of Norman Fairclough's Critical Discourse Analysis in 3 stages: Text Analysis (Description), Discursive Practice (Interpretation), Social Practice (Explanation). We aim to understand how this unique digital narrative is created and shared. The findings of this study reveal that digital media weaves narratives that highlight religious tourism, heritage preservation, and Islamic spirituality, thereby influencing public perception of the Saka Tunggal Mosque. However, there are challenges, such as the risk of historical inaccuracy due to the spread of unverified information and the potential loss of the authentic meaning of the mosque amidst the commercialization of tourism. Ultimately, this study explains how digital media acts as a bridge in shaping the identity of a religious place and suggests ways to improve digital communication strategies to maintain its historical meaning.